Surgical Services during Pandemic Era in the Most Remote Part in Indonesia - Heru Sutanto Koerniawan; Freda Halim; Prajnaariayi Prawira; Irene Waine (Cermin Dunia Kedokteran, 2021)
The coronavirus disease 2019 (COVID-19) pandemic has brought unprecedented adaptations and changes in global healthcare management. The pandemic has created major dilemmas for health care workers in all health care areas including surgical services. To avoid any local transmission, the risk level of all surgical patients is evaluated before, or immediately after admission. Changes have been made based on the availability of the hospital resources, as best as possible, based on the protocol developed by WHO and the Ministry of Health Republic of Indonesia. Pandemi penyakit coronavirus 2019 (COVID-19) menyebabkan adaptasi dan perubahan manajemen pelayanan kesehatan di seluruh dunia. Pandemi ini telah menyebabkan dilema besar bagi pekerja kesehatan di semua bidang termasuk pelayanan bedah. Untuk mencegah transmisi lokal, semua pasien bedah dinilai tingkat risikonya sebelum, atau sesaat setelah di dalam rumah sakit. Beberapa protokol dan manajemen pelayanan kesehatan di Indonesia telah dibuat dan diterapkan berdasarkan tersedianya sumber daya di rumah sakit dan sedapat mungkin mengikuti protokol WHO dan Kementrian Kesehatan Republik Indonesia.